PERBAIKAN TATA LETAK PENYIMPANAN SPARE PART MESIN PRODUKSI DENGAN METODE CLASS BASED STORAGE PADA GUDANG PT. ULTRA PRIMA PLAST - Sri Mukti Wirawati; Sri Ndaru Arthawati; Opandi Opandi (Tirtayasa Ekonomika, 2017)
In carrying out the production process the company does not only rely on human power, but also the need for equipment and machinery. To meet the overwhelming consumer demand, PT. Ultra Prima Plast company engaged in flexible packaging always maintain and care for the machines used in the production process, one of which is by storing spare parts for production machines, performance of spare part storage systems in warehouse with uncluttered conditions, spare parts exceed the capacity of cabinets and irregular in spare part storage not based on the characteristics of the use of the spare part itself and the list of spare part systems, causing problems when going to repair the machine, because technicians have difficulty finding the items to be used. Therefore it is necessary to repair the spare part storage layout by using the Class Based Storange method (storage based on class / group) which can make it easier for technicians to find the spere parts that will be used. The data used for analysis are warehouse spare part data, spare part characteristic data and arrival data and use of spare parts as primary data. The results obtained from the analysis of space requirements (space) width of the spare part is 21,995 meters, the amount of available wide space is 27.2 meters, so the space effectiveness can be as much as 5,205 meters andthe final result is spare parts grouped by type and use as well as acceleration of discovery